Localized Automorphisms and Endomorphisms - Hassan, Abdelgabar Adam (Communications in Mathematics and Applications, 2023)
We give a practical criterion of invertibility of endomorphisms of \(O_n\) corresponding to unitaries in the normalizer of the diagonal inside the uniformly hyperfinite subalgebra. We also analyze the action of such localized automorphisms on the spectrum of the diagonal thus obtaining criteria of outerness. Unital endomorphisms of the Cuntz algebra \(O_n\) which preserve the canonical uniformly hyperfinite-subalgebra \(F_n \subseteq O_n\) are investigated. We give examples of such endomorphisms \(λ =λ_u\) for which the associated unitary element \(u\) in \(O_n\).
Keywords: Algebra; Endomorphism; Automorphism; Uniformly hyperfinite; Cuntz algebra